Cyclical Strikes and Human Capital Accumulation under Asymmetric Information - Piergiuseppe Fortunato (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2001)
Strikes are totally inefficient from an economic point of view. They occur when the two parties that bargain over a contract do not find an agreement and the result is a loss of utility for both. In spite of their clear inefficiency in the real world strikes are very common both in the rich economies as well as in the poor countries. Moreover, recent empirical literature found some regularities over time and over countries regarding the strike behavior of the Trade Unions. The aim of this paper is to develop a theory that could explain this apparent economic paradox as well as some of the most known regularities. At the same time we also aim to link the analysis of the strikes with the investment decisions of employers and workers in that particular kind of capital good known as Human Capital. This kind of approach can put under a new light the role played by the Trade Unions in the process of economic growth.
Keywords: 330